Neuroinflammation and Behavior in HIV-1 Transgenic Rats Exposed to Chronic Adolescent Stress - Rowson, Sydney A.; Harrell, Constance S.; Bekhbat, Mandakh; Gangavelli, Apoorva; Wu, Matthew J.; Kelly, Sean D.; Reddy, Renuka; Neigh, Gretchen N. (Frontiers in Psychiatry, 2016)
Highly active antiretroviral therapy (HAART) has improved prognosis for people living with HIV (PLWH) and dramatically reduced the incidence of AIDS. However, even when viral load is controlled, PLWH develop psychiatric and neurological disorders more frequently than those living without HIV. Adolescents with HIV are particularly susceptible to the development of psychiatric illnesses and neurocognitive impairments. While both psychiatric and neurocognitive disorders have been found to be exacerbated by stress, the extent to which chronic stress and HIV-1 viral proteins interact to impact behavior and relevant neuroinflammatory processes is unknown. Determination of the individual contributions of stress and HIV to neuropsychiatric disorders is heavily confounded in humans. In order to isolate the influence of HIV-1 proteins and chronic stress on behavior and neuroinflammation, we employed the HIV-1 transgenic (Tg) rat model, which expresses HIV-1 proteins with a gag and pol deletion, allowing for viral protein expression without viral replication. This Tg line has been characterized as a model of HAART-controlled HIV-1 infection due to the lack of viral replication but continued presence of HIV-1 proteins. We exposed male and female adolescent HIV-1 Tg rats to a mixed-modality chronic stress paradigm consisting of isolation, social defeat and restraint, and assessed behavior, cerebral vascularization, and neuroinflammatory endpoints. Stress, sex, and presence of the HIV-1 transgene impacted weight gain in adolescent rats. Female HIV-1 Tg rats showed decreases in central tendency during the light cycle in the open field regardless of stress exposure. Both male and female HIV-1 Tg rats exhibited decreased investigative behavior in the novel object recognition task, but no memory impairments. Adolescent stress had no effect on the tested behaviors. Microglia in female HIV-1 Tg rats exhibited a hyper-ramified structure, and gene expression of complement factor B was increased in the hippocampus. In addition, adolescent stress exposure increased microglial branching and junctions in female wild-type rats without causing any additional increase in HIV-1 rats. These data suggest that the presence of HIV-1 proteins during development leads to alterations in behavioral and neuroinflammatory endpoints that are not further impacted by concurrent chronic adolescent stress.